1986
DOI: 10.1002/pssb.2221330106
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of raman scattering in Cd3As2 single crystals

Abstract: Raman scattering measurements in the tetragonal CdSAs, single crystals are carried out a t temperatures of 300 and 77 K. The spectra obtained are interpreted in terms of phonon-electron and electron-electron interactions. The features in the low-frequency interval are due to contributions from phonon and single particle scattering. The electronic RS involving intra-and interband excitations is dominant a t frequencies higher than 80 cm-l. The resonant enhancement of the band a t 300 cm-l arises from the incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
9
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 11 publications
6
9
0
Order By: Relevance
“…A consistent blueshift of ≈15 cm −1 that is evident for both modes points to a residual compressive strain induced as a result of platelet cooling, Figure 3 , the inset. The lowest, high intensity mode at 210 cm −1 (195 cm −1 in target) coincides with 196 cm −1 phonon-allowed mode reported by Jandl et al [ 19 ] and Weszka et al, [ 20 ] whereas the largest intensity mode at 265 cm −1 (249 cm −1 in target) was also predicted and reported to exist in α-Cd 3 As 2 by Weszka. [ 20 ] The bulk crystal structure of Cd 3 As 2 ( a = 1.267 nm and c = 2.548 nm) comprises a face-centered cubic lattice for As with six Cd atoms occupying the eight corners of an inner cube (two diagonally opposite corners of a cubic face remain empty).…”
supporting
confidence: 85%
“…A consistent blueshift of ≈15 cm −1 that is evident for both modes points to a residual compressive strain induced as a result of platelet cooling, Figure 3 , the inset. The lowest, high intensity mode at 210 cm −1 (195 cm −1 in target) coincides with 196 cm −1 phonon-allowed mode reported by Jandl et al [ 19 ] and Weszka et al, [ 20 ] whereas the largest intensity mode at 265 cm −1 (249 cm −1 in target) was also predicted and reported to exist in α-Cd 3 As 2 by Weszka. [ 20 ] The bulk crystal structure of Cd 3 As 2 ( a = 1.267 nm and c = 2.548 nm) comprises a face-centered cubic lattice for As with six Cd atoms occupying the eight corners of an inner cube (two diagonally opposite corners of a cubic face remain empty).…”
supporting
confidence: 85%
“…We find an additional peak at 178 cm À1 and two more modes at around 300 cm À1 , which coincide with a mode at 300 cm À1 reported by Weszka et al 13 The authors did not comment on the satellite peak at 309 cm À1 , which has half of the intensity of the main peak. 13 III-V compound nanowires are usually grown in a selfcatalyzed process with or without a group-III element acting catalytically and being located at the tip of the nanowire. It was shown that the presence of the catalytic tip depends on the group-V flux during cool-down.…”
supporting
confidence: 83%
“…However, the low frequency parts of the two RS spectra should be due to modes with predominant Zn contribution involved. This corresponds quite well with the mode frequency values observed for Cd,As, [7] and Zn,As, [8] crystals in which Cd(Zn)-As bonds exist only, as well as those for tetragonal ZnP, [5] (with spiral P chains). However, further studies both theoretical and experimental are needed for a better understanding of the lattice dynamics of monoclinic ZnAs,.…”
Section: Discussionsupporting
confidence: 86%